Management of Praja's Reading Culture Development Through Website Media Promotion at The Campus Library of Institut Pemerintahan Dalam Negeri Jatinangor - Annisa Susinta (Universitas Airlangga, 2022)
Management of reading culture development starts from reading - thinking - writing activities. The use of websites can take advantage of librarians to encourage interest in reading and writing for users. The librarian's task is to act as a driving force for collaborative innovation in literacy creation in the use of libraries in the form of a reading fondness movement. This article aims to describe the function of reading culture management through the promotion of media websites and IPDN digital library catalogs. The method used in this research is a qualitative method with literature study and direct observation. Using an interdisciplinary scientific approach. The results of the study found that librarians as literacy drivers and university libraries that facilitated the movement of reading fondness played a very important role in supporting the reading culture of students/users in maximizing library utilization by promoting through websites that display attractive websites, online journal portals, Kubuku applications, and Ebsco used to attract readers to be interested in reading